Racial, Socioeconomic, and Payer Status Disparities in Utilization of Total Ankle Arthroplasty Compared with Ankle Arthrodesis - Jessica Schmerler BS; Suraj Dhanjani; Alyssa Wenzel MD; Shyam J. Kurian MD; Uma Srikuaran MD MBA MPH; James Ficke MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: Total ankle arthroplasty is increasingly being used for the treatment of ankle osteoarthritis when compared to arthrodesis. However, there has been limited investigation into disparities in utilization of these comparable procedures. This study examined racial/ethnic, socioeconomic, and payer status disparities in the likelihood of undergoing total ankle arthroplasty compared with ankle arthrodesis. Methods: Patients with a diagnosis of ankle osteoarthritis from 2006 through 2019 were identified in the National Inpatient Sample, then subclassified as undergoing total ankle arthroplasty or arthrodesis. Multivariable logistic regression models, adjusted for hospital location, total hospital charges, primary or secondary osteoarthritis diagnosis, and patient characteristics (age, sex, infection, diabetes, neuropathy, and Elixhauser Comorbidity Index), were used to examine the effect of race/ethnicity, socioeconomic status, and payer status on the likelihood of undergoing total ankle arthroplasty versus arthrodesis. Results: There were 6,966 patients who underwent TAA and 5,681 patients who underwent arthrodesis over the study period. Black and Hispanic patients were 42% and 32% less likely than White patients to undergo total ankle arthroplasty rather than arthrodesis (P <.001). Patients in income quartiles 3 and 4 were 17% and 23% more likely, respectively, than patients in quartile 1 (the lowest quartile) to undergo total ankle arthroplasty rather than arthrodesis (P=.001 and P=0.01, respectively). Privately insured and Medicare patients were 67% and 117% more likely, respectively, than Medicaid patients to undergo total ankle arthroplasty rather than arthrodesis (P <.001). Conclusion: Racial/ethnic, socioeconomic, and payer status disparities exist in the likelihood of undergoing total ankle arthroplasty versus arthrodesis for ankle osteoarthritis. More work is needed to establish drivers of these disparities and identify targets for intervention, including improvements in parity in relative procedure utilization.